2009
DOI: 10.3324/haematol.2009.013920
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting long-term survival after T-cell depleted reduced intensity allogeneic stem cell transplantation for acute myeloid leukemia

Abstract: BackgroundReduced intensity conditioning regimens permit the delivery of a potentially curative graft-versus-leukemia effect in older patients with acute myeloid leukemia. Although T-cell depletion is increasingly used to reduce the risk of graft-versus-host disease its impact on the graft-versusleukemia effect and long-term outcome post-transplant is unknown. Design and MethodsWe have characterized pre-and post-transplant factors determining overall survival in 168 patients with acute myeloid leukemia transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 32 publications
2
69
2
2
Order By: Relevance
“…28 Given the close relationship between GVHD and GVL, this study sought to assess the impact of GVHD on outcome in a large and rather homogeneous cohort of AML patients given PBSC after various RIC, and particularly at assessing the impact of GVHD on survival given the divergent results observed in studies containing fewer number of patients. [10][11][12][20][21][22][23][24] Several observations could be drawn from the current findings. First, current study observed a positive impact (that is, lower risk of relapse translating into better LFS) of grade I acute GVHD on transplantation outcomes in patients given RIC allo-SCT for AML.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…28 Given the close relationship between GVHD and GVL, this study sought to assess the impact of GVHD on outcome in a large and rather homogeneous cohort of AML patients given PBSC after various RIC, and particularly at assessing the impact of GVHD on survival given the divergent results observed in studies containing fewer number of patients. [10][11][12][20][21][22][23][24] Several observations could be drawn from the current findings. First, current study observed a positive impact (that is, lower risk of relapse translating into better LFS) of grade I acute GVHD on transplantation outcomes in patients given RIC allo-SCT for AML.…”
Section: Discussionmentioning
confidence: 57%
“…However, this is a delicate balance as a number of prior studies have shown a lower risk of relapse in AML patients who experienced chronic GVHD after RIC allo-SCT compared with those patients who did not, [10][11][12]20,21 while some other studies failed to find such an association. 22,23 A recent analysis from the Center for International Blood and Marrow Transplant Research (CIBMTR) analyzed the impact of GVHD in a cohort of patients with AML or myelodysplastic syndrome given various graft types after RIC conditioning. 24 In a landmark analysis at 1 year after transplantation (n ¼ 630), relapse incidence was reduced only in the group of patients with prior both acute and chronic GVHD, while acute and/or chronic GVHD had no significant impact on disease-free survival.…”
Section: Introductionmentioning
confidence: 99%
“…Low exposure to CNI the first weeks after transplantation 13 -Increases GV-AML effects -Increases risk of GvHD?…”
Section: Mechanisms Of Action Potential Limitationsmentioning
confidence: 99%
“…11,12 Given the poor prognosis of patients who experience relapse after allo-HCT, several groups of investigators have assessed various post-transplant approaches aimed at preventing disease relapse in high-risk AML patients (Table 1). These approaches include decreasing the level of post-grafting immunosuppression, 13 preemptive (i.e., administered in patients with post-transplant evidence of minimal residual disease or low / decreasing donor chimerism levels) or prophylactic administration of diseasespecific medications such as demethylating agents 14 or FLT3 inhibitors, 15 or preemptive 16,17 or prophylactic DLI. 18,19 In this issue of Bone Marrow Transplantation, Jedlickova et al 20 report the results of a retrospective analysis assessing the safety and efficacy of prophylactic DLI in a cohort of 46 high-risk AML patients given grafts following a sequential treatment consisting of chemotherapy (FLAMSA) followed by RIC allo-HCT.…”
mentioning
confidence: 99%
“…17,23 Taken together, with the profoundly adverse impact of multiple co-morbidities on transplant outcome, our data allow the identification of a population of older patients with active disease in whom allogeneic transplantation is very unlikely to deliver a survival benefit. As a consequence, these data now inform clinical practice at the reporting centres and patients with a HCT-CI of greater than 1 are only transplanted in exceptional circumstances or according to an investigational protocol.…”
Section: Discussionmentioning
confidence: 99%